Harold and the purple crayon [videorecording (DVD)] - Guion, David; Handelman, Michael; Levi, Zachary, 1980-; Howery, Lil Rel, 1979-; Bottani, Benjamin; Clement, Jemaine; Reynolds, Tanya, 1991-; Molina, Alfred, 1953-; Deschanel, Zooey, 1980-; Beristain, Gabriel; Sener, Batu; Johnson, Crockett, 1906-1975 (Sony Pictures Home Entertainment, 2024)
Inside of his book, adventurous Harold can make anything come to life simply by drawing it. After he grows up and draws himself off the book₂s pages and into the physical world, Harold finds he has a lot to learn about real life, and that his trusty purple crayon may set off more hilarious hijinks than he thought possible. When the power of unlimited imagination falls into the wrong hands, it will take all of Harold and his friends' creativity to save both the real world and his own.